NITROGEN SLIGHTLY REDUCES GHG PRODUCTION FROM INCUBATED PEAT SAMPLES - Böhm, Marianne; Potthast, Karin; Baysinger, Mackenzie Rae (2024)
Peatland soils are projected to respond to rising global temperatures with an increase in microbial respiration rates. At the same time, nutrients that were previously bound in undecomposed organic matter will increasingly become available to the decomposer microbial communities. The pathway and magnitude of response in respiration rates to a changing nutrient status remains an open question, especially given that these ecosystems are typically limited in nutrients like nitrogen. In my ongoing Master thesis, I investigate the effects of adding nitrate and ammonium to incubated peat samples from Siikaneva bog in boreal Finland. While the site itself is not affected by permafrost, this study provides an analogue for the future of peatlands at the edge of the permafrost zone. Preliminary results from 190 days of incubation indicate that carbon dioxide production was reduced by ammonia additions. Data on methane production were less conclusive, but also point to an average reduction of total C respiration. Samples from above and below the water table exhibit different trajectories, which may be an expression of different microbial communities: most prominently, a complete lack of methanogenenis in the surface samples. In summary, this implies that the peatland carbon sink is not endangered by nutrient release.